Code Mixing and Code Switching in Movie Murder on the Orient Express by Kenneth Branagh - Wahdini Fauzana; Saidatun Nafisah; Widya Widya (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
This research aims to identify types of code-switching and code-mixing found in some of “Murder on The Orient Express” movie dialogues and utterances. The source of the data in this research is the dialogue in Murder on The Orient Express movie. To achieve the aims of this research; the researcher uses the descriptive qualitative research method. This study uses the code-switching theory of Wardhaugh (1986) and code-mixing theory of Suwito (1983). There are two types of code-switching consisting of metaphorical code-switching and situational code-switching and two types of code-mixing consisting of outer code-mixing and inner code-mixing. From the results of this study, the authors found 50 data of code-mixing and code-switching and as many as 4 or 8% metaphorical code-switching data, 2 or 4% situational code-switching data. The author also found 44 or 88% outer code-mixing data, and 0 or 0% inner code-mixing data. The research’s result shows that the dominant form of code-switching and code-mixing is metaphorical code-switching and outer code-mixing.